Verification the dichotomy of democracy-despotism relating ancient Iran and Greece - Hamidi, Mohammad Mohsin (Technium Social Sciences Journal, 2021)
Iran and Greece have played major roles in ancient world and are seen as two rival power and sometimes enemies. In political thought and structure, in political and historical texts, they are seen also different, one is democratic model and another is an empire and autocracy, but there is some resemblance between their political views that are neglected. Also some mistakes there are. What same socio-political contexts has been in both? This article is addressed this main point.